Framing the Interpersonal Communication of Chronic Kidney Disease Patients Underwent Hemodialysis with Their Partners on Sexual Dysfunction - Saptyasari, Andria (UI Scholars Hub, 2021)
This study elaborates on how patients with chronic kidney disease and their partners provide stimulation and response to sexual dysfunction problems using the relationship framing theory. Previous research has shown that 20-30% of patients with stage 3-5 chronic kidney disease undergoing hemodialysis experience sexual dysfunction. This study assumes that sexual dysfunction can lead to decreased sexual desire, commitment, and proximity between patients and their partners which impact their interpersonal communication. This study is interpretive qualitative research which applied an in-depth interview method. Relationship framing theory was used to explore the content dimensions related to the topics of passion, commitment, and proximity to describe the relationship dimensions, which are related to dominance-submissiveness and affiliation-disaffiliation of the participants’ utterances. The results show that the content dimensions consisting of passion, closeness, and commitment between chronic kidney disease patients and their partners could frame the relationship between them by looking at the stimulus and respective responses related to these three things. The stimuli and responses between these couples differ because there are four factors that influence it, namely (1) the context of the problem that is framed; (2) relational context; (3) sincerity of the participants in accepting the conditions; (4) partner’s sensitivity regarding empathy; and (5) values, religion and spiritual which both patients and their partners have.